Early growth response-1, a dynamic conduit in cardiovascular disease - Khachigian, Levon M. (Frontiers in Cardiovascular Medicine, 2024)
The transcription factor, early growth response-1 (Egr-1) is the product of a prototypic immediate-early gene that plays an integral role in the pathogenesis of multiple cardiovascular diseases. Egr-1 has been linked with atherogenesis, myocardial ischemia-reperfusion injury, cardiac fibrosis and heart failure. Egr-1 expression is triggered by a host of factors including cytokines, hormones, growth factors, hyperglycaemia, biomechanical forces and oxygen deprivation. Egr-1 is a molecular conduit that links changes in the cellular environment with the inducible expression of genes whose products play a causative role in this inflammatory disease. It is rapidly synthesised, undergoes post-translational modification, interacts with a range of cofactors and drives gene expression. Studies in Egr-1 deficient mice, animal models using DNAzymes, RNA interference, oligodeoxynucleotide decoys, antisense oligonucleotides, and new insights provided by technologies such as single cell RNA sequencing, have shaped our understanding of the importance of Egr-1 in the initiation and progression of cardiovascular disease. This article describes Egr-1’s role in various cardiovascular settings and discusses potential mechanisms of action. Given the range of conditions linked to Egr-1, this zinc finger protein may serve as a therapeutic target for intervention.